[m-4][m-8]+3 因式分解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 11:36:40
[m-4][m-8]+3因式分解[m-4][m-8]+3因式分解[m-4][m-8]+3因式分解[m-4][m-8]+3=[(m-6)+2][(m-6)-2]+3=(m-6)^2-2^2+3=(m-6
[m-4][m-8]+3 因式分解
[m-4][m-8]+3 因式分解
[m-4][m-8]+3 因式分解
[m-4][m-8]+3
=[(m-6)+2][(m-6)-2]+3
=(m-6)^2-2^2+3
=(m-6)^2-1^2
=[(m-6)+1][(m-6)-1]
=(m-5)(m-7)
[m-4][m-8]+3
=[(m-6)+2][(m-6)-2]+3
=(m-6)^2-2^2+3
=(m-6)^2-1^2
=[(m-6)+1][(m-6)-1]
=(m-5)(m-7)
我是老师 谢谢采纳
[m-4][m-8]+3 因式分解
m^3-2m^2-4m+8 因式分解
m/3+9m^4因式分解
因式分解(3^4)^m÷27^m
m^2-4m+3怎么因式分解
因式分解:3m^2+4m-2
因式分解:m^3减4m
因式分解(m^2+3m)^4-8(m^2+3m)^2+16
m^4-4m^3+4m^2-9因式分解
-4m³16m²+8m 因式分解
m^2-4m+8-2m^2 因式分解
m³-2m²-4m+8因式分解,
因式分解m^3-4m^2+4m
因式分解-4m^3-16m^2-2m=
因式分解 -m³+3m²+4m
(m^4-81)/(3+m)/(9+m^2)因式分解
因式分解 m^2-4m
因式分解m的3次方-2m平方-4m+8=